Peran Guru BK dalam Mengurangi Perilaku Siswa Mencontek - Yasin Muhammad Syibli; Sapari, Sapari (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2021)
This study aims to determine the role of counseling teachers in reducing student cheating behavior at MTs Nurul Huda Munjul Cirebon, to determine the shape of the role of counseling teachers, and to determine the obstacles and ways to reduce student cheating behavior in class VIII-A at MTs Nurul Huda Munjul Cirebon. The subjects in this study were the principal, supervisors and students. This type of research is qualitative research, which examines the role of counseling teachers in reducing student cheating behavior in the classroom. This research has also obtained results that the role of counseling teachers in reducing student cheating behavior in class VIII-A MTs Nurul Huda Munjul Cirebon has a positive impact. The Guiding Teacher performs its role by providing information services and group guidance to students, by providing information material related to reducing student cheating behavior and group guidance services that can train them to reduce their cheating habit. Implementation of this guidance and counseling service is carried out by a counseling teacher who is supported by the cooperation of the homeroom teacher, subject teacher, student deputy head of the student division and the principal. The role of counseling teachers creates positive reactions from the behavior and mindset of students. Teachers feel happy and feel helped in reducing student cheating behavior, and students are more enthusiastic in following the implementation of guidance and counseling, and have knowledge of the bad cheating behavior. The role of the guidance and counseling teacher aims to provide more insight into the bad behavior of cheating, so that students can think again when they want to cheat, and at least students reduce their habit of cheating during the exam. The role of the guidance and counseling teacher has obstacles due to the unavailability of a special counseling schedule for classrooms and the absence of a counseling room